SELECTION CRITERIA FOR PROJECT MANAGEMENT APPROACHES IN SOFTWARE DEVELOPMENT - KAMENSKA, MARIA; LAVRIK, VOLODYMYR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
In today's dynamic technological landscape, effective project management is a critical success factor in software engineering. This paper presents a comparative analysis of three widely used project management methodologies: Waterfall, Scrum, and Kanban. Based on key evaluation criteria—such as flexibility, documentation, risk management, change management, teamwork, planning, and testing—each methodology's strengths and limitations are thoroughly examined. A structured comparison table highlights how these approaches differ and under what circumstances each proves most effective. The research shows that the Waterfall model is a linear and sequential approach ideal for projects with clearly defined, stable requirements, where thorough documentation and predictability are essential. However, its rigidity makes it less adaptable to change. Scrum, an iterative framework, is highly responsive to changes and fosters close team collaboration, but it demands strong discipline and may not be suitable for projects with tight, inflexible deadlines. Kanban focuses on continuous workflow and visual task management, providing high flexibility and responsiveness but making time prediction and long-term planning more challenging. The paper provides practical recommendations for selecting the appropriate methodology depending on project type, uncertainty level, and team priorities. It concludes that no single approach is universally optimal. Instead, choosing the right methodology requires a deep understanding of the project's nature and the ability to balance structure and adaptability. Applying the most suitable methodology can significantly enhance software development efficiency, reduce risks, and ensure successful project delivery in today’s competitive environment.
Keywords: project management; Waterfall; Agile; Scrum; Kanban; IT projects